2000
DOI: 10.1038/sj.ejhg.5200507
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of the Ellis–van Creveld region on chromosome 4p16 in some families with asphyxiating thoracic dystrophy and short-rib polydactyly syndromes

Abstract: Ellis-van Creveld syndrome (EVC) is a relatively rare, usually non-lethal, autosomal recessive skeletal dysplasia characterized by short stature, polydactyly, cardiac and renal anomalies. Linkage analysis has localized the disease gene to chromosome 4p16, with the markers at loci D4S827 and D4S3135 defining the centromeric and telomeric limits of the linked interval, respectively. There has been long-term speculation that asphyxiating thoracic dystrophy (ATD) and the short-rib polydactyly syndromes (SRP) repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…When it is present, the postaxial polydactyly occurs most frequently in the distribution of bilateral hands and feet. The frequency of hepatic problems occurs in <30% of reported cases, and it is difficult to predict risk of developing liver disease based upon the presence of skeletal findings [Karjoo et al, 1973;Friedman et al, 1975;Oberklaid et al, 1977;Shah, 1980;Turkel et al, 1985;Hudgins et al, 1990;Labrune et al, 1999;Krakow et al, 2000;Kajantie et al, 2001;Ö zçay et al, 2001;Morgan et al, 2003;Yerian et al, 2003;Tuysuz et al, 2009;De Vries et al, 2010;Lehman et al, 2010]. In addition, from review of the literature, most cases with hepatic structural changes are identified at autopsy, but are usually clinically mild, stable, or resolve with therapy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When it is present, the postaxial polydactyly occurs most frequently in the distribution of bilateral hands and feet. The frequency of hepatic problems occurs in <30% of reported cases, and it is difficult to predict risk of developing liver disease based upon the presence of skeletal findings [Karjoo et al, 1973;Friedman et al, 1975;Oberklaid et al, 1977;Shah, 1980;Turkel et al, 1985;Hudgins et al, 1990;Labrune et al, 1999;Krakow et al, 2000;Kajantie et al, 2001;Ö zçay et al, 2001;Morgan et al, 2003;Yerian et al, 2003;Tuysuz et al, 2009;De Vries et al, 2010;Lehman et al, 2010]. In addition, from review of the literature, most cases with hepatic structural changes are identified at autopsy, but are usually clinically mild, stable, or resolve with therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Further both SRPS III and a mild form Jeune syndrome were reported in a consanguineous family [Ho et al, 2000]. Because of suggestion that Jeune syndrome and SRPS type III may represent a spectrum of disorders with EvC syndrome, Krakow et al [2000] performed and showed no linkage with markers from 4p in seven families having ATD or SRPS III. Rinaldi et al [1990] reported two sisters with cystinuria and Jeune syndrome suggesting there may be linkage between the two genes causing these conditions.…”
Section: Discussionmentioning
confidence: 96%
“…SRPS III is phenotypically related to asphyxiating thoracic dystrophy (ATD [MIM 208500]) and Ellis-van Crefeld syndrome (EVC [MIM 225500]). Indeed, all three disorders share similar radiological features, including short ribs and polydactyly [8,9]. However, SRPS III is more severe and is associated with early prenatal expression, severely shortened tubular bones with round metaphyseal ends bearing lateral spikes, and lethality.…”
Section: Introductionmentioning
confidence: 95%
“…Patients with SRP could have mutations in the EVC2 gene. However, we excluded linkage to the EvC region on chromosome 4p in one family with SRP III [Krakow et al, 2000]. With our unbiased sample, we conclude that mutations in the coding region of EVC1 do not account for the majority of cases of EvC, and SRP III is probably due to a defect in a gene other than EVC1 or EVC2.…”
Section: To the Editormentioning
confidence: 71%
“…Radiographically and histologically, SRP III most resembles some forms of EvC [Yang et al, 1987]. The question of SRP being due to disruption of a gene in the 4p16 region where EvC maps was raised [Urioste et al, 1994], but we were able to exclude it in one family with SRP III by linkage analysis [Krakow et al, 2000]. It remained possible that some SRP III cases could have mutations in the EVC1 gene.…”
Section: To the Editormentioning
confidence: 97%